Biomechanical implications of the onset of walking. Issue 122 (September 2018) - Cowgill, Libby W.; Johnston, Rob'yn A.
Abstract: Changes in long bone strength associated with the onset of bipedal walking in humans have been previously documented in a longitudinal growth sample. However, it is unclear if this transition can be detected using archaeological, cross-sectional data, which likely encompass more cultural and biological variation than a single dataset of living children. Focusing on variation in cross-sectional polar second moment of area, we evaluate the ratios of femoral, tibial, and humeral strength in seven temporally diverse samples of individuals from birth to the age of eighteen years ( n = 501), with subsequent comparisons to immature Late Pleistocene fossils. Using these samples, we determine whether changes related to the developmental onset of bipedality can be detected in a large, multi-population sample, test for differences in long bone strength ratios among Holocene groups that may indicate developmental differences in the onset of walking, and determine whether immature Late Pleistocene samples follow the same patterns as modern humans. Despite great variation within the Holocene sample, clear changes in these ratios are apparent around the age of the onset of walking. Humeral-to-femoral strength increases briefly prior to the age of one, with a sharp decline in relative humeral strength thereafter until age four. A similar pattern is apparent in the ratio of humeral/tibial and femoral/tibial strength. While the general pattern is consistent across all human groups sampled, these ratios vary by skeletal population, which seems to be closely related to variation in tibial length among samples. Although the extremely small fossil sample makes differences difficult to interpret, Neandertals also differ from both Late Pleistocene and Holocene modern humans in their strength ratios. Further research in this area may provide additional information about the skeletal impact of the onset of walking in the past and in additional fossil taxa.